Theory of Bose-Einstein condensation and superfluidity of two-dimensional polaritons in an in-plane harmonic potential - Berman, Oleg L.; Lozovik, Yurii E.; Snoke, David W. (Physical review. B, Condensed matter and materials physics, 2008)
Recent experiments have shown that it is possible to create an in-plane harmonic potential trap for a two-dimensional (2D) gas of exciton polaritons in a microcavity structure, and evidence has been reported of Bose-Einstein condensation of polaritons accumulated in this type of trap. We present here the theory of Bose-Einstein condensation (BEC) and superfluidity of the exciton polaritons in a harmonic potential trap. Along the way, we determine a general method for defining the superfluid fraction in a 2D trap, in terms of angular momentum representation. We show that in the continuum limit, as the trap becomes shallower, the superfluid fraction approaches the 2D Kosterlitz-Thouless limit, while the condensate fraction approaches zero, as expected.